2003
DOI: 10.1086/374739
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Herpesvirus and Polyomavirus Reactivation and Shedding in Healthy Adults: A 14‐Month Longitudinal Study

Abstract: Humans are infected with viruses that establish long-term persistent infections. To address whether immunocompetent individuals control virus reactivation globally or independently and to identify patterns of sporadic reactivation, we monitored herpesviruses and polyomaviruses in 30 adults, over 14 months. Epstein-Barr virus (EBV) DNA was quantitated in saliva and peripheral blood mononuclear cells (PBMCs), cytomegalovirus (CMV) was assayed in urine, and JC virus (JCV) and BK virus (BKV) DNAs were assayed in u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
93
3
3

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(108 citation statements)
references
References 55 publications
9
93
3
3
Order By: Relevance
“…EBV infection is generally controlled by the immune system in healthy individuals, but the virus remains latent in circulating B lymphocytes (19,20). Viral reactivation can occur in seropositive-normal individuals, resulting in viral shedding in the oropharynx (21). Although it is estimated that 90% of the healthy adult population is seropositive for EBV, reactivation occurs in only 10-20% of This article is a PNAS Direct Submission.…”
Section: Resultsmentioning
confidence: 99%
“…EBV infection is generally controlled by the immune system in healthy individuals, but the virus remains latent in circulating B lymphocytes (19,20). Viral reactivation can occur in seropositive-normal individuals, resulting in viral shedding in the oropharynx (21). Although it is estimated that 90% of the healthy adult population is seropositive for EBV, reactivation occurs in only 10-20% of This article is a PNAS Direct Submission.…”
Section: Resultsmentioning
confidence: 99%
“…These data are consistent with other studies that showed high CMV and EBV salivary shedding among more immunosuppressed patients in comparison with HIV-seronegative individuals 4,7,10 . Even in patients submitted to HAART, EBV and CMV shedding appears to persist at a higher frequency compared with HIV-uninfected controls 8,12 . This finding is in agreement with other studies in Brazil that also showed a high prevalence of CMV and EBV in HIV-seropositive patients 10;35 .…”
Section: Ethicalmentioning
confidence: 96%
“…The frequencies of these viruses are wide-ranging, varying from 62 to 90% for EBV; 57% for HHV-8; 19 to 72% for CMV and 5 to 16 for HSV-1 4,7,[10][11][12] . In these reports, the prevalence of HHVs was higher in HIV-seropositive patients than seronegative individuals.…”
Section: Article/artigomentioning
confidence: 99%
“…Reactivation of JCV can occur in otherwise healthy individuals and leads to asymptomatic viruria (57,58). A study investigating patterns of sporadic reactivation showed that JCV infections are persistent, and that healthy persons older than age 40 years commonly shed the virus in urine (59).…”
Section: Polyomavirusmentioning
confidence: 99%